2000
DOI: 10.1161/01.cir.102.24.2952
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficacy of Eptifibatide Administration in Patients With Acute Coronary Syndrome Requiring In-Hospital Coronary Artery Bypass Grafting

Abstract: Eptifibatide administration in patients undergoing in-hospital CABG with a recent episode of a non-ST-segment elevation acute coronary syndrome results in a significant reduction in death or MI that is evident at 7 days and persists through the 6-month follow-up without a significant increase in perioperative bleeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…An analysis of the PURSUIT trial by Marso et al 87 showed that CABG not only is safe in these patients who initially received eptifibatide therapy, but it also resulted in improved outcomes. The reduction in rates of 6-month death or MI was from 35.3% to 23.8% with eptifibatide therapy in patients undergoing CABG within 72 hours of initiation of the study drug (P=.009).…”
Section: Treatment Strategy For Unstable Angina or Non-q-wave MImentioning
confidence: 99%
“…An analysis of the PURSUIT trial by Marso et al 87 showed that CABG not only is safe in these patients who initially received eptifibatide therapy, but it also resulted in improved outcomes. The reduction in rates of 6-month death or MI was from 35.3% to 23.8% with eptifibatide therapy in patients undergoing CABG within 72 hours of initiation of the study drug (P=.009).…”
Section: Treatment Strategy For Unstable Angina or Non-q-wave MImentioning
confidence: 99%
“…15 The results from the placebo group in the surgical arm of the PURSUIT trial (30% re-infarction or death rate at 30 days postoperatively) clearly indicates that something is amiss regarding the present mainstream myocardial protection strategies, particularly for patients with acute coronary syndrome. 16 The importance of improving the myocardial management of ischemic cardiac tissue, including implanted cardiac allografts, cannot be overstated. We believe it is possible to further improve 1-, 3-and 5-year survival rates and also extend the safe ischemia times for such grafts with further modifications of myocardial protection, and thus we are currently studying the effects of controlled oxygen exposure in transplanted allografts at the University of Chicago.…”
mentioning
confidence: 99%
“…In addition, ischemic complications within 30 days were less frequent among abciximab-treated patients, with a 42% lower rate of death or Q-wave MI. Results obtained from a subgroup of PUR-SUIT patients undergoing CABG within 72 hours of initiation of eptifibatide have shown a 6-month reduction in the rate of MI or death of 35.3% (eptifibatide) compared with 23.8% (control), with no difference in the risk of major bleeding (56.7% placebo vs 58.2% eptifibatide, P = 0.70) [59]. Similar safety and efficacy was demonstrated for tirofiban by Barr et al [42] in a subanalysis of PRISM-PLUS patients.…”
Section: Glycoprotein Iib/iiia Inhibitors and Coronary Bypass Surgerymentioning
confidence: 99%